"Building strength in coming together": A mixed methods study using the arts to explore smoking with staff working in Indigenous tobacco control. (5th July 2018) - Gould, Gillian S.; Stevenson, Leah; Bovill, Michelle; Oliva, Dora; Keen, Jennifer; Dimer, Lyn; Gruppetta, Maree
Abstract: Issue addressed: Tobacco is a major risk factor contributing to Indigenous health disparities. Art may be a powerful and transformative tool to enable health providers to develop targeted messages for tobacco control. Methods: Indigenous and non‐Indigenous staff, working in Indigenous tobacco control, attended a 2‐hour workshop, and were led through a process to create individual artworks. Participants completed surveys before and after the workshop. Scales compared understandings of how art can be used in tobacco control, and the likelihood of utilising arts in future programs. Three pairs of Indigenous and non‐Indigenous researchers analysed the artworks, using the Four Frames (New South Wales Board of Studies), explored themes, and developed a model. Results: Nineteen participants completed both surveys; 17 artworks were analysed. Pre‐ to post‐workshop increases in "understanding" about the use of arts ( P < 0.00001) for tobacco control, and "likelihood" of use of arts in the next 6 months ( P < 0.006) were significant. Participants expressed personal and professional benefits from the workshop. Artworks demonstrated themes of optimism, the strength of family and culture, smoking as a barrier, resilience, recovery and urgency. Conclusions: The workshop increased the understanding and likelihood of using the arts for tobacco control. Artworks revealed contemporary challenges impacting on equity; health staff expressed optimism for being engaged in their work. So what?: The Framework Convention for Tobacco Control supports novel techniques to increase the reach and relevance of health messages for diverse populations. This study successfully demonstrated how a novel, positively framed art‐based technique proved to be advantageous for health professionals, working in an area of Indigenous tobacco control, where behavioural change can be complex.